TRANSLATION SHIFTS IN â€œPERCY JACKSON AND OLYMPIANS: THE LIGHTNING THIEFâ€ NOVEL BY RICK RIORDAN - Regina Seliana; Priska Meilasari (Humaniora Scientia, 2023)
This research focuses on the theory of translation shifts and accuracy of translation. The data were analyzed through the theory of translationby Catford Â (1965), namely unit shifts, structural shifts, intra-system shifts, class shifts, and level shifts from English (SL) to Indonesian (TL). The problems discussed in this research are the types of translation shifts used in translating the novel â€œPercy Jackson and Olympians: The Lightning Thiefâ€as well as how accurate the translation is. To solve the problem, a qualitative descriptive method was applied in this research. The data is taken from the novel â€œPercy Jackson and Olympians: The Lightning Thiefâ€written in English and translated into Indonesian. The result of data analysis found that there were as many as 107 data. The most dominant data found in the novel is unit shift with 50 data, structure shift with 36 data, Â intra-system shift with 8 data, class shift with 8 data, and Â level shift with 4 data. In addition, the researcher also found 104 data were considered accurate translations, 3 data were considered less accurate translations, and none were inaccurate.Â Keywords: Translation, translation shift, translation accuracy